Dentigerous Cyst in Children: A Case Report and Outline of Clinical Management for Pediatric and General Dentists - Zakirulla, M; Yavagal, CM; Jayashankar, DN; Meer, Allahbaksh (Journal of Orofacial Research, 2012)
Dentigerous cysts are the most common developmental odontogenic cysts of the jaw, arising from impacted, embedded or unerupted permanent teeth. They apparently develop byaccumulation of fluid between the reduced enamel epithelium and the tooth crown of an unerupted tooth. There is usually no pain or discomfort associated with the cyst unless there is an acute inflammatory exacerbation. Careful evaluation, coupled with meticulous clinical and radiological investigations could help clinicians to arrive at the correct diagnosis as well as address the implicated etiologies, before instituting the most appropriate therapy. Here, we report a case of a dentigerous cyst in the mixed dentition of a 10-year-old female patient and outline its comprehensive management for the benefit of pediatric and general dentists involved in the care of such patients.